PENGETAHUAN DAN PERILAKU TENTANG KEBERSIHAN GIGI DAN MULUT PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS ABULYATAMA - Andri Andri; Isfanda Isfanda (Jurnal Sains Riset, 2021)
Dental and oral health in Indonesian society needs to be considered. In Indonesia, dental and mouth disease are among the top ten diseases spread across the region. From the data of bogor health office in 2009 showed 231,227 (21.78%) of total 1,061,440 city dwellers suffering from dental and mouth disease. From year to year there was an increase in the prevalence rate of caries incidence in Indonesia population by 63% to 90%. For that reason caries in indonesia requires serious handling from various parties. The purpose of this research is to know the knowledge and behavior about dental hygiene at faculty of university doctoral skill of abulyatama year 2017. This research is descriptive with cross sectional study design which conducted on 6 s / d 10 july year 2017. Respondent is 68 respondents Proportional sampling is obtained by using a questionnaire that has been designed. In general, the results showed the knowledge about oral hygiene in the faculty students of abulyatama university dormitory in 2017, which is in the good category of 69 respondents (83.1%), the behavior of oral hygiene at university students of abulyatama university medical school in 2017, Which is in the good category that is 58 respondents (69.9%), knowledge and behavior about dental hygiene at university student of abulyatama medical university year 2017, which is in less category that is 57 respondent (68.7%), based on above result it is expected To all students to always keep dental and oral hygiene to avoid tooth decay and bad breath.Keywords: Knowledge, Behavior, Tooth and Mouth Hygiene